Disturbance-specific social responses in long-finned pilot whales, Globicephala melas: - Visser, F.; Curé, C.; Kvadsheim, P.H.; Lam, F.P.A.; Tyack, P.L.; Miller, P.J.O. (Nature Publishing Group, 2016)
Social interactions among animals can influence their response to disturbance. We investigated responses of long-finned pilot whales to killer whale sound playbacks and two anthropogenic sources of disturbance: Tagging effort and naval sonar exposure. The acoustic scene and diving behaviour of tagged individuals were recorded along with the social behaviour of their groups. All three disturbance types resulted in larger group sizes, increasing social cohesion during disturbance. However, the nature and magnitude of other responses differed between disturbance types. Tagging effort resulted in a clear increase in synchrony and a tendency to reduce surface logging and to become silent (21% of cases), whereas pilot whales increased surface resting during sonar exposure. Killer whale sounds elicited increased calling rates and the aggregation of multiple groups, which approached the sound source together. This behaviour appears to represent a mobbing response, a likely adaptive social defence against predators or competitors. All observed response-Tactics would reduce risk of loss of group coordination, suggesting that, in social pilot whales, this could drive behavioural responses to disturbance. However, the behavioural means used to achieve social coordination depends upon other considerations, which are disturbance-specific.